Barcelona and the food. Unpublished images of the twentieth century - Mària, Magda (E|C, 2020)
Food in public space has been a constant presence in the city of Barcelona, arousing the interest of painters and photographers who for decades have proposed their personal visions on forms, times, customs or activities around food and urban life. This article is the summary of a research that has collected more than 1,560 images from the main archives and museums of the city, mostly unpublished, made during the twentieth century. The drawings, engravings, paintings and photographs have been grouped diachronically into five thematic groups ranging from the relationship of food to the streets and squares of the city, to the closest and most detailed relationship between food and domestic space. In all it is noted that food-related activities have always been present in the urban landscape of Barcelona, temporarily or permanently changing its appearance. And we see how some of its manifestations remain virtually intact, others have undergone great changes, and some have disappeared altogether.